Deep Brain Stimulation of the Nucleus Accumbens in Severe Enduring Anorexia Nervosa: A Pilot Study - Scaife, Jessica C.; Eraifej, John; Green, Alexander L.; Petric, Beth; Aziz, Tipu Z.; Park, Rebecca J. (Frontiers in Behavioral Neuroscience, 2022)
Introduction: Anorexia nervosa is one of the most debilitating psychiatric disorders, becoming severe and enduring in a third of cases; with few effective treatments. Deep brain stimulation is a reversible, adjustable neurosurgical procedure that has been gaining ground in psychiatry as a treatment for depression and obsessive compulsive disorder, yet few studies have investigated anorexia nervosa. Abnormal eating behaviour and the compulsive pursuit of thinness in anorexia nervosa is, in part, a consequence of dysfunction in reward circuitry and the nucleus accumbens is central to reward processing. Methods: Phase 1 prospective open-label pilot study of seven individuals with severe enduring anorexia nervosa. Electrodes were implanted bilaterally into the nucleus accumbens with stimulation at the anterior limb of the internal capsule using rechargeable implantable pulse generators. The protocol of 15 months included 12 months of deep brain stimulation incorporating two consecutive, randomized blind on-off fortnights 9 months after stimulation onset. The primary objectives were to investigate safety and feasibility, together with changes in eating disorder psychopathology. Results: Feasibility and safety was demonstrated with no serious adverse events due to deep brain stimulation. Three patients were responded to treatment (defined as >35% reduction in Eating Disorders Examination (EDE) score at 12 months) and four patients were non-responders. Responders had a statistically significant mean reduction in EDE scores (50.3% reduction; 95% CI 2.6% to 98.2%), Clinical Impairment Assessment (45.6% reduction; 95% CI 7.4% to 83.7%). Responders also had a statistically significant mean reduction in Hamilton Depression Scale, Hamilton Anxiety Scale and Snaith-Hamilton pleasure scale. There were no statistically significant changes in Body Mass Index, Yale-Brown-Cornell Eating Disorder Scale, Yale-Brown Obsessive-Compulsive Scale and World Health Organisation Quality of Life Psychological subscale. Conclusions: Selected patients with severe enduring anorexia nervosa can benefit from deep brain stimulation to the nucleus accumbens. In this small study, the three responders had comorbid obsessive compulsive disorder which predated anorexia nervosa diagnosis. Future studies should aim to further elucidate predictors of outcome. Clinical Trial Registration: The study is registered with www.ClinicalTrials.gov, https://clinicaltrials.gov/ct2/show/NCT01924598, 22 July, 2013. It has full ethical and HRA approval (Project ID 128658).